3. RISK FACTORS AND USAGE OF VENOUS THROMBOSIS PROPHYLAXIS IN SURGICAL PATIENTS AT CAN THO CITY ONCANCER HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate the risk factors and use of prophylactic drugs for venous thromboembolism in surgical patients at Can Tho City Oncology Hospital.Materials and methods: Cross-sectional descriptive study on 255 patients with indications for elective surgery at Can Tho City Oncology Hospital. The study subjects were surveyed based on a pre-designed questionnaire.Results: The rate of surgical patients at high risk of venous thromboembolism was 62.7%. Common risk factors for venous thromboembolism were: age group 41-60, BMI >25, malignancy and surgery time longer than 45 minutes. The rate of patients prescribed postoperative anticoagulants was 24.7%. The rate of patients prescribed preoperative anticoagulants was 0%. Statistical analysis showed that there was a relationship between postoperative anticoagulant use and surgical site, the difference was statistically significant with p
Keywords: venous thromboembolism prevention; risk stratification; venous thromboembolism; Can Tho City Oncology Hospital